2009
DOI: 10.1016/j.jcrs.2008.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Toric intraocular lens versus opposite clear corneal incisions to correct astigmatism in eyes having cataract surgery

Abstract: Toric IOL implantation achieved a slight enhanced effect over OCCIs in treating preexisting astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 43 publications
11
119
0
2
Order By: Relevance
“…Likewise, our results in terms of predictability of refractive correction were also comparable to those reported for other modalities of toric IOLs [5][6][7][8] and in some cases even better. 9,10 Visser et al 9 found that residual refractive astigmatism of -1.00 D or less was achieved in approximately 90% of samples of eyes implanted with a toric multifocal IOL.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, our results in terms of predictability of refractive correction were also comparable to those reported for other modalities of toric IOLs [5][6][7][8] and in some cases even better. 9,10 Visser et al 9 found that residual refractive astigmatism of -1.00 D or less was achieved in approximately 90% of samples of eyes implanted with a toric multifocal IOL.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, treatments like selective suture removal, relaxing incisions, wedge resections, compression sutures, photorefractive keratectomy (PRK), and laser-assisted in situ keratomileusis (LASIK) all serve as feasible options in correcting astigmatism. [2][3][4][5] There is emerging evidence advocating the use of customized toric intraocular lens (IOL) as a novel approach to correct high post-PK astigmatism. 6,7 Not uncommonly, patients with post-PK astigmatism can also develop cataract in the previously operated eye at the later stage of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Each degree of rotation causes an average loss of cylinder power of approximately 3%; thus, when an IOL rotates 30 degrees there is no astigmatic correction, although there is a change of axis (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) . Articles comparing the use of toric IOL to other astigmatism reducing techniques, such as opposed clear corneal incisions (56) or LRI (57) , are still scanty in number on literature. Slightly advantageous outcomes, favoring toric IOL have been reported (56,57) , but debate on which technique unequivocally offers better results is just at the beginning.…”
Section: B) Non-incisional Approachmentioning
confidence: 99%
“…Articles comparing the use of toric IOL to other astigmatism reducing techniques, such as opposed clear corneal incisions (56) or LRI (57) , are still scanty in number on literature. Slightly advantageous outcomes, favoring toric IOL have been reported (56,57) , but debate on which technique unequivocally offers better results is just at the beginning. Toric IOL may also be employed in conjunction to such techniques aiming further refractive improvements (38) .…”
Section: B) Non-incisional Approachmentioning
confidence: 99%